Heme oxygenase and the immune system in normal and pathological pregnancies - Ozen, Maide; Zhao, Hui; Lewis, David B.; Wong, Ronald J.; Stevenson, David K. (Frontiers in Pharmacology, 2015)
Normal pregnancy is an immunotolerant state. Many factors, including environmental, socioeconomic, genetic, and immunologic changes by infection and/or other causes of inflammation, may contribute to inter-individual differences resulting in a normal or pathologic pregnancy. In particular, imbalances in the immune system can cause many pregnancy-related diseases, such as infertility, abortions, pre-eclampsia, and preterm labor, which result in maternal/fetal death, prematurity, or small-for-gestational age newborns. New findings imply that myeloid regulatory cells and regulatory T cells (Tregs) may mediate immunotolerance during normal pregnancy. Effector T cells (Teffs) have, in contrast, been implicated to cause adverse pregnancy outcomes. Furthermore, feto-maternal tolerance affects the developing fetus. It has been shown that the Treg/Teff balance affects litter size and adoptive transfer of pregnancy-induced Tregs can prevent fetal rejection in the mouse. Heme oxygenase-1 (HO-1) has a protective role in many conditions through its anti-inflammatory, anti-apoptotic, antioxidative, and anti-proliferative actions. HO-1 is highly expressed in the placenta and plays a role in angiogenesis and placental vascular development and in regulating vascular tone in pregnancy. In addition, HO-1 is a major regulator of immune homeostasis by mediating crosstalk between innate and adaptive immune systems. Moreover, HO-1 can inhibit inflammation-induced phenotypic maturation of immune effector cells and pro-inflammatory cytokine secretion and promote anti-inflammatory cytokine production. HO-1 may also be associated with T-cell activation and can limit immune-based tissue injury by promoting Treg suppression of effector responses. Thus, HO-1 and its byproducts may protect against pregnancy complications by its immunomodulatory effects, and the regulation of HO-1 or its downstream effects has the potential to prevent or treat pregnancy complications and prematurity.